NON-ALTERNATIVE LEXICON IN THE VOCABULARY OF THE LANGUAGE AND ITS LINGUISTIC AND EXTRALINGUISTIC BASIS - Shamshetova Biybiayim Janibekovna (Journal of new century innovations, 2022)
Abstract. The article aims to investigate the concept of non-alternative lexicon, its linguistic and extralinguistic basis. The findings of the research depicts that non- alternative lexicon has a great impact on language system. The use of non-alternative lexicon in linguistics and extralinguistics is of huge importance. Therefore, it should be fully analyzed and special features ought to be taken into account.